BRAND NARRATIVE DYNAMICS AND CONSUMER LOYALTY IN THE SOCIAL MEDIA ERA: UNCOVERING THE ROLE OF EMOTIONAL ENGAGEMENT AND DIGITAL INTERACTION - Hery Margono (UIN Sunan Gunung Djati Bandung, 2025)
The development of social media has transformed the way brands communicate with consumers, shifting from one-way communication to more open and participatory interactions. In an increasingly dynamic digital environment, brand narratives evolve through various forms of conversation involving consumers as part of the communication process taking place in the public sphere. This makes emotional engagement and digital interactions crucial elements influencing how consumers build relationships with brands on social media. This study aims to analyze the dynamics of brand narratives within the social media ecosystem and their role in shaping consumer loyalty through emotional engagement and digital interactions. This study uses a qualitative approach, reviewing various literature sources and previous research relevant to the topics of brand communication, digital interactions, and consumer behavior on social media. The results indicate that brand narratives develop through a dialogic communication process between brands and consumers in the digital space. Consumer emotional engagement and participation in digital interactions play a role in strengthening the relationship between consumers and brands. Consistent and ongoing communication experiences on social media ultimately contribute to the formation of consumer trust and loyalty towards brands.